Elucidating the real effect of Ba and Co doping on the magnetic and optical properties of BiFeO3. Issue 7 (August 2015) - Rojas-George, G.; Concha-Balderrama, A.; Silva, J.; Fuentes, L.; Reyes-Rojas, A.
Abstract: We present Ba/Co co-doping effects on BiFeO3 structure, optical, ferromagnetic, and ferroelectric properties at room temperature. XRD indicates a high distortion of the rhombohedral symmetry, confirmed by Raman spectroscopy, where a change in the intensity ratio of E-1/A1 -1 vibrational modes is a result of the partial substitution of Fe 3+ by Co 3+ . This induces an A-site disorder in the FeO6 octahedra. Co 2+ acts as grain growth inhibitor reducing average grain sizes from 304 nm (without cobalt) to 200 nm (with cobalt) after sintering. The magnetization results show that the Co-cation impregnated samples have higher magnetization (31%) than doped and undoped samples.